2007
DOI: 10.1007/s10526-007-9130-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of diet and photoperiod on development and reproduction of European populations of Harmonia axyridis (Pallas) (Coleoptera: Coccinellidae)

Abstract: The current study examines the effect of photoperiod (16:08 or 12:12 h L:D) and diet (eggs of Ephestia kuehniella Zeller (Lepidoptera: Phycitidae) or the pea aphid Acyrthosiphon pisum (Harris) (Hemiptera: Aphididae)) on the development and reproduction of the multicoloured Asian lady beetle Harmonia axyridis (Pallas) (Coleoptera: Coccinellidae). A long-term laboratory population of H. axyridis (since 1998) and a melanic and non-melanic population originating from field collected individuals of H. axyridis in B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
49
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 35 publications
4
49
0
2
Order By: Relevance
“…Hodek (1973) Hodek (1973), pois permitiram o desenvolvimento, a oviposição e a sobrevivência da joaninha. Estudos têm demonstrado que ovos de E. kuehniella, S. cerealella e A. kuehniella são eficientes dietas para a criação de Coccinellidae (Kato et al, 1999;Abdel-Salam & Abdel-Baky, 2001;Berkvens et al, 2008b). No presente trabalho, a dieta com ovos de A. kuehniella foi adequada para criação de H. axyridis.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Hodek (1973) Hodek (1973), pois permitiram o desenvolvimento, a oviposição e a sobrevivência da joaninha. Estudos têm demonstrado que ovos de E. kuehniella, S. cerealella e A. kuehniella são eficientes dietas para a criação de Coccinellidae (Kato et al, 1999;Abdel-Salam & Abdel-Baky, 2001;Berkvens et al, 2008b). No presente trabalho, a dieta com ovos de A. kuehniella foi adequada para criação de H. axyridis.…”
Section: Resultsunclassified
“…A joaninha-asiática Harmonia axyridis Pallas, 1773 (Coleoptera: Coccinellidae) é considerada uma predadora voraz e eficaz, principalmente de pulgões, e tem sido utilizada como agente de controle biológico em várias culturas, na América do Norte e Europa (Brown & Miller, 1998;Michaud, 2000;Kuroda & Miura, 2003;Landis et al, 2004;Berkvens et al, 2008b).…”
Section: Introductionunclassified
“…Moreover, they found that H. axyridis entered hibernation with an empty gut. Berkvens et al (2008) were able to induce a reproductive diapause in the fourth generation of a laboratory-reared population collected in the field in April 2005. However, they could not replicate this with individuals that were field-collected in June 2008 (Berkvens et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Hatching rate (percentage of eggs 1196 that hatch to the first larval instar) should be calculated over the first month of reproduction, since it 1197 declines strongly later (Awad et al 2013). Hatching rate in H. axyridis in different countries varied 1198 from 15% in Belgium (Berkvens et al 2008) to 100% in Italy (unpublished data), although it has not 1199 been measured in most countries (Table 2). Hatching success may depend on many factors for 1200 example food source, colour morph, endosymbionts and multiple fertilisation.…”
mentioning
confidence: 99%